INFLUENCE ОF MODIFIER THERMAL TREATMENT ОN CHARACTERISTICS ОF COMPOSITE MATERIALS FOR PROTECTIVE COATINGS - V. Ivashko; A. Vorontsov (Наука и техника)
This paper presents results that reveal influence of modifiers characterized by different nature and composition and subjected to heat treatment on operational characteristics of single and binary compositions. Interaction between dispersed clay particles and dependence of  coating properties on  their mass content in oligomeric and polymeric matrices have been justified in the paper. The paper contains data that prove an increase of coating hardness by 15–20 %. The coating composition includes thermally-treated dispersed clay particles.